2021
DOI: 10.3892/etm.2021.10311
|View full text |Cite
|
Sign up to set email alerts
|

Interference of long non‑coding RNA HAGLROS inhibits the proliferation and promotes the apoptosis of ovarian cancer cells by targeting miR‑26b‑5p

Abstract: Ovarian cancer (OV) is the fifth most common type of cancer affecting women worldwide. Long non-coding RNAs (lncRNAs) serve essential roles in the progression of OV. As such, the present study aimed to investigate the specific role of HAGLR opposite strand lncRNA (HAGLROS) in OV and the underlying mechanism of action through which HAGLROS exerts its effects on OV cells. In the present study, the expression of HAGLROS in several OV cell lines was first detected using reverse transcription-quantitative PCR. HAGL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…Gene ontology of the PRINS lncRNA-miRNA-mRNA under study revealed that the axis is functioning mainly in the regulation of cytokine production involved in the inflammatory response, gene silencing by miRNA, and regulation of gene expression, data in line with previous studies [37,[44][45][46][47][48][49][50][51][52][53][54][55]. The biological functions are correlated with the molecular function as the LncRNA-miRNA-mRNA under study are involved in gene silencing at both the transcriptional and post-transcriptional levels by binding to transcription factor, TAT protein (a regulator of gene expression), mRNA 3′-untranslated region, and large and small ribosomal subunits .…”
Section: Discussionsupporting
confidence: 85%
“…Gene ontology of the PRINS lncRNA-miRNA-mRNA under study revealed that the axis is functioning mainly in the regulation of cytokine production involved in the inflammatory response, gene silencing by miRNA, and regulation of gene expression, data in line with previous studies [37,[44][45][46][47][48][49][50][51][52][53][54][55]. The biological functions are correlated with the molecular function as the LncRNA-miRNA-mRNA under study are involved in gene silencing at both the transcriptional and post-transcriptional levels by binding to transcription factor, TAT protein (a regulator of gene expression), mRNA 3′-untranslated region, and large and small ribosomal subunits .…”
Section: Discussionsupporting
confidence: 85%
“…Lin et al. reported that knockdown HAGLROS can suppress the proliferation and promote the apoptosis of ovarian cancer cells by regulating miR-26b-5p, which affects the expression of apoptosis-related proteins ( 24 ). Notably, recent study indicated that HAGLROS was highly expressed and decreasing HAGLROS can inactivate the mTOR axis and elevate autophagy through improving lipid metabolism reprogramming in intrahepatic cholangiocarcinoma ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…That is to say, HAGLROS could exert tumor-promoting role in HCC by sponging miR-26b-5p. A similar document found that interference of HAGLROS repressed the proliferation and induced the apoptosis of ovarian cancer cells by targeting miR-26b-5p [ 38 ]. However, the effects of HAGLROS on cell migration and invasion, and tumor growth were not investigated.…”
Section: Discussionmentioning
confidence: 99%